Pengembangan Sistem Informasi Buku Saku Karakter Berbasis Android (Studi Kasus: SD UMP Purwokerto) - Ahmadan Mukhtarif; Buce Trias Hanggara; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Character Building is currently a major concern in education. Characters are developed or taughtthrough education, social training and interpersonal experiences. To monitor the developmentnecessary information system is effective and in accordance with technological developments. Thepurpose of this research is to design an application to monitor the character development ofelementary school students through Android-based character Pocket book information System. Thecharacter Pocket Book application uses WebServices as an intermediary between applications andservers. The application will request data to the webservices, which then the request will be forwardedto the server. After the server provides a response to WebServices, webservices then converts the datainto JSON format, so that it can be read by Android applications. The programming language that isused is Extensible Markup Language (XML). The design of systems undertaken include: (1)architectural design; (2) sequence diagram; and (3) interface planning. The implementation of thesystem is: (1) implementation of functions and (2) interface implementation. While the testing ofinformation systems that have been made, to know the level of conformity of systems with therequirement specification is done, by teachers, parents and students of SD UMP. Based on the resultsof user acceptance testing, using the Functional code and Completeness indicators, and Usability, it isknown that the respondent's acceptance rate of the application is above 80%. It can be concluded thatGuru, student and guardian students can receive and use the Android-based character Pocket bookinformation System app.